Education in and for the Belt and Road Initiative: The Pedagogy of Collective Writing. Issue 10 (23rd August 2020) - A. Peters, Michael; Oladele, Ogunniran Moses; Green, Benjamin; Samilo, Artem; Lv, Hanfei; Amina, Laimeche; Wang, Yaqian; Chunxiao, Mou; Chunga, Jasmin Omary; Rulin, Xu; Ianina, Tatiana; Hollings, Stephanie; et al.
Abstract: This paper is an experiment in collective writing conducted in Autumn 2019 at the Faculty of Education at Beijing Normal University. The experiment involves 12 international masters' students reading the course based on the Belt and Road Initiative (BRI), their professor Michael Peters, visiting professor Petar Jandrić, and a mix of senior Chinese and Western scholars. To successfully complete the course, the students were required to produce a 3000-word paper of publishable quality. As part of this writing process we decided to engage in the experiment of collective writing where we aimed to produce a single paper consisting of the abstracts. This collective paper was developed in 7 steps. (1) Students submitted their 250-word abstracts. (2) Students were introduced into the methodology of collective writing, and 2 student-editors – Ogunniran Moses Oladele and Benjamin Green – volunteered to work on the paper. (3) Michael Peters wrote the introduction. (4) Abstracts were expanded to 500 words and integrated into a single document. (5) Petar Jandrić began to edit the paper and write a conclusion. (6) Students presented their abstracts in the class, where Michael Peters and Petar Jandrić provided direct feedback. (6) Revised abstracts were again integrated into a single document by student editors, and proofread / copy-edited in several exchanges with the instructors (7) The paper was subject to the process of open review, and the reviewer's comments were included in the paper. Resulting from months of collective work, the final paper provides a wide range of views ad perspectives to the question of education as a part of the BRI initiative.